TINGKAT PARTISIPASI APARATUR SIPIL NEGARA (ASN) SEBAGAI KOMPONEN CADANGAN DALAM RANGKA MEMPERKUAT PERTAHANAN NEGARA - Prita Nurwahyu; Hendra Felani; Nanang Hery Soebagijo; Hikmat Zakky Al-Mubaroq; Christine Sri Marnani (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2022)
Abstract In order to maintain the sovereignty and territorial integrity of a country, a strong and resilient defense is needed to deal with threats that may come from outside the country or within the country, carried out by state actors and non-state actors. Indonesia adheres to a universal defense system (Sishanta), which is a defense system that involves all components of the nation to participate in national defense efforts because actually defense efforts are not only the responsibility of members of the Indonesian National Armed Forces (TNI) but also the rights and obligations of all Indonesian people in particular. The State Civil Apparatus (ASN), is a tool of the state and functions as a unifier of the nation. Sishanta consists of three components, namely: main components, spare components, and supporting components. The Ministry of State Apparatus Empowerment and Bureaucratic Reform (MenPAN-RB) issued circular letter No. 27 of 2021 as a legal basis for ASN participation in national reserve component training (Komcad), ASN is expected to join Komcad in order to strengthen national defense. The research method used is a descriptive research method with a qualitative approach by conducting a literature review. The results showed that ASN participation in the Komcad program was still very low at only 0.05% of the total ASN who met the age requirements to register. Keywords: National defense, Reserve component, State Civil Apparatus